Advancing Sustainable Tourism Ecosystem Management: The Case of Destination Resilience in Kerora, Rinca & South Padar at Komodo National Park Area, Flores, Indonesia - Fransiskus Xaverius Teguh; Steve Noakes (Politeknik Pariwisata Makassar, Indonesia, 2026)
This research article aims to examine the strengthening of sustainable tourism ecosystem management through the development of community-based destination resilience models, focusing on three main interventions: human-animal conflict mitigation, ecosystem restoration (land reforestation and coral reef restoration), and community empowerment. This study deploys a descriptive qualitative approach with data triangulation techniques through in-depth interviews, field observations, and documentation studies carried out in Kerora Village, Rinca Village, and South Padar, all located within the Komodo archipelago, Indonesia. The findings of the study show that the integration of conservation programs with the specific needs of local communities can encourage adaptive capacity building, strengthening social cohesion, and more efficient management of ecological risks with the number of conflict incidents decreased to about 70 %. The novelty of this study lies in the formulation of a destination resilience cycle model that includes four main stages: participatory planning, implementation of community-based interventions, impact control through visitor management, and adaptive evaluation. This model not only strengthens the effectiveness of conservation area governance, but also opens up opportunities for replication in other destinations with similar socio-ecological characteristics. The results of this study provide a theoretical contribution to the development of sustainable tourism ecosystem management models that are more contextual, regenerative, and collaborative.